Integration along the Abuja road map: A progress report - Jaime De Melo; Mariem Nouar; Jean-Marc Solleder (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
This paper reviews integration among the eight African Regional Economic Communities by comparing their characteristics and progress with three other South-South Regional Integration Arrangements. Three conclusions emerge: (i) slow progress towards meeting overly ambitious objectives; (ii) small changes in the destination of trade across all Regional Economic Communities, indicative of persistent high trade costs and few new manufactures products destined for geographically close markets; and (iii) compared with other South-South Regional Integration Arrangements, the Regional Economic Communities include a high number of provisions not covered in Word Trade Organization negotiations, but these have low legal enforceability. Reasons for this slow progress are explored in the paper.
Keywords: F13; F55; F63; 330; gravity model; Regional Economic Communities; Regional Integration Arrangements; trade costs